Tindak Pidana Kejahatan Pencucian Uang (Money Laundering) dalam Pandangan KUHP dan Hukum Pidana Islam - Geno, Ali (TAWAZUN: Journal of Sharia Economic Law, 2019)
Money Laundering is an attempt to hide or disguise the origin of money or assets resulting from a criminal act through various financial transactions so that the money or assets appear as if they came from legal activities. There are three stages taken to " purification" the proceeds of crime in laundring money. First, the money generated from a crime activity is changed into a form that does not or does not arouse suspicion through placement in the financial system in various ways (placement). The second step is to conduct financial transactions that are complex, layered and anonymous with the aim of separating the proceeds of crime from various sources so that it is difficult to trace the origin of the fund which in other words hides or disguises the origin of the proceeds of crime (layering). The last step is the stage where the actor re-enters funds that have escaped their origins into Assets that appear legitimate both to be enjoyed directly, invested in various forms of material and financial assets, used to finance legitimate business activities or to refinance activities criminal act (integration).